Electrospun TiO2 Nanofibers Surface‐Loaded with Ag Nanoparticles as a Sensitizer and Their Enhanced Effect in Photocatalytic Applications. Issue 30 (18th September 2015) - Zhang, Li; Wang, Lei; Wei, Yuan; Zhang, Mingyue; Jiang, Haifeng; Li, Jianing; Li, Shu; Li, Junfeng
Abstract: In this work, Ag–TiO2 nanofibers were prepared by a simple electrospinning and photoreduction method. A mechanism for the synthesis of the Ag–TiO2 nanofibers was proposed on the basis of XRD, X‐ray photoelectron spectroscopy (XPS), SEM, and energy‐dispersive X‐ray spectroscopy (EDX) results. The photocatalytic activities of the nanofibers were characterized for the degradation of aqueous solutions of methyl orange (MO) and hydrogen evolution from water with methyl alcohol as a sacrificial reagent under the simulated sunlight irradiation. The results indicate that the Ag‐modified TiO2 nanofibers are efficient and stable photocatalysts for dye degradation and hydrogen evolution. Compared with pure TiO2 nanofibers, the Ag–TiO2 composite nanofibers have higher photocatalytic activities, and the best load of Ag was 5 mol‐%. The Ag nanoparticles serve as charge‐transfer sites and broaden the spectral absorption band of the catalyst. Abstract : TiO2 is a high‐performance catalyst for photocatalytic degradation and hydrogen evolution. However, its wide band gap and the fast recombination of the photogenerated electron–hole pairs limit its applications. Ag nanoparticles are loaded onto TiO2 nanofibers by photoreduction to enhance the photocatalytic efficiency of the catalyst. The optimum Ag loading is 5 %.